2013
DOI: 10.3126/stcj.v1i1.7985
|View full text |Cite
|
Sign up to set email alerts
|

The effects of cigarette smoking on hemoglobin levels compared between smokers and non-smokers

Abstract: Background: Smoking is one of the global problems causing different disease. Smoking cause variation in different parameters of blood among which hemoglobin is believed to be increased due to smoking. Objective: To compare the effect of cigarette smoking on hemoglobin levels between smokers and non smokers. Materials and methods: A cross-sectional comparative study was conducted in Department of Pathology, Hematology Laboratory, B.P. Koirala Institute of Health Sciences, Dharan, Nepal. Total of 100 sample size… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
18
0
7

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 9 publications
7
18
0
7
Order By: Relevance
“…The CS causes a decrease in blood O 2 levels. As a result, the body increases the production of red blood cells (erythrocytes, hemoglobin, and hematocrit) to compensate for the decrease in oxygen carrying capacity 46. These data corroborate our results, as there was an increase in red blood cell levels in the CS compared with CG.…”
Section: Discussionsupporting
confidence: 90%
“…The CS causes a decrease in blood O 2 levels. As a result, the body increases the production of red blood cells (erythrocytes, hemoglobin, and hematocrit) to compensate for the decrease in oxygen carrying capacity 46. These data corroborate our results, as there was an increase in red blood cell levels in the CS compared with CG.…”
Section: Discussionsupporting
confidence: 90%
“…The association of substance use and levels of education has been reported worldwide. 13,14 The majority of participants belonged to lower socioeconomic status which is in congruence with the existing literature. 15 Tobacco is a cheap and easily available substance.…”
Section: Discussionsupporting
confidence: 86%
“…It is reported that erythrocyte count in adult male smokers is increased with minimum amount of smoking when compared with non-smokers [6]. Smoking increase concentration of hemoglobin in blood and it is due to CO exposure [7]. According to the study current smokers show significantly higher level of WBCs count as compared to non-smokers or passive smokers [8].…”
Section: Introductionmentioning
confidence: 94%